2017
DOI: 10.1104/pp.17.00310
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling of Wheat Inflorescence Development from Spikelet Initiation to Floral Patterning Identified Stage-Specific Regulatory Genes

Abstract: Early reproductive development in cereals is crucial for final grain number per spike and hence the yield potential of the crop. To date, however, no systematic analyses of gene expression profiles during this important process have been conducted for common wheat (Triticum aestivum). Here, we studied the transcriptome profiles at four stages of early wheat reproductive development, from spikelet initiation to floral organ differentiation. K-means clustering and stage-specific transcript identification detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
108
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(120 citation statements)
references
References 101 publications
10
108
0
Order By: Relevance
“…However, the allohexaploid wheat genome makes genetic dissection highly challenging. Recent breakthroughs in genome sequencing have enabled transcriptome analysis possible for this important food crop (Feng et al, 2017;Li et al, 2014). In this study, we analyzed the transcriptomes of young spikes in 90 winter wheat lines and correlated expression with variations in spike complexity traits (spikelet number per spike, floret number per spike, and seed number per spike).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the allohexaploid wheat genome makes genetic dissection highly challenging. Recent breakthroughs in genome sequencing have enabled transcriptome analysis possible for this important food crop (Feng et al, 2017;Li et al, 2014). In this study, we analyzed the transcriptomes of young spikes in 90 winter wheat lines and correlated expression with variations in spike complexity traits (spikelet number per spike, floret number per spike, and seed number per spike).…”
Section: Resultsmentioning
confidence: 99%
“…In wheat, increased transcription levels of Q, an AP2-like gene, was markedly associated with spike compactness, suggesting that the Q gene may be implicated in spike development (Simons et al, 2006), although its role in spike complexity remains unclear. Feng et al (2017) reported that a durum wheat ARGONAUTE1d gene mutant produced shorter spikes and fewer grains per spike than wild-type controls. In addition, recent studies have shown the mechanisms underlying the genetic regulation of rare supernumerary spikelet variations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Three RNA‐seq papers (Lister et al ., ; Mortazavi et al ., ; Nagalakshmi et al ., ) on Arabidopsis, yeast and mice, respectively, mark the start of this tool's use for functional genomic studies. Contemporarily, RNA‐seq is used at ever‐larger scales for functional characterization of developmental, environmental response and economically important phenotypes (Becker et al ., ; Feng et al ., ; Giacomello et al ., ; Leydon et al ., ; Liu et al ., ), and is often used to validate epigenomic measurements (Wang et al ., ). There are numerous studies that employ whole‐genome gene expression analysis not just for model plant species and crops, but also for lesser‐known plant species including Japanese lawn grass (Xie et al ., ), Cunninghamia lanceolata (Cao et al ., ), mangrove fern (Zhang et al ., ), wild oil‐tea camelia (Chen et al ., ), curry tree (Meena et al ., ) and Banksia (He et al ., ).…”
Section: The Transcriptome Shapes Trait Variationmentioning
confidence: 99%
“…This treatment hydrolyzes the long polysaccharide chain to smaller fractions to increase their solubility. Moreover, in a study, soluble dietary fiber content in black soybean hull was increased by using hydrogen peroxide (Feng et al, ). Furthermore, the dietary fiber ratio of whole grain barley was modified by carboxymethylation (Park, Lee, & Lee, ).…”
Section: Introductionmentioning
confidence: 99%